Fortifying the Treatment of Prostate Cancer with Physical Activity - Colin E. Champ; Lanie Francis; Rainer J. Klement; Roger Dickerman; Ryan P. Smith (Prostate Cancer)
Over the past decade, significant data have shown that obese men experience a survival detriment after treatment for prostate cancer. While methods to combat obesity are of utmost importance for the prostate cancer patient, newer data reveal the overall metabolic improvements that accompany increased activity levels and intense exercise beyond weight loss. Along these lines, a plethora of data have shown improvement in prostate cancer-specific outcomes after treatment accompanied with these activity levels. This review discusses the metabolic mechanisms in which increased activity levels and exercise can help improve both outcomes for men treated for prostate cancer while lowering the side effects of treatment.